POTENSI KITOSAN SEBAGAI PENGAWET PRODUK HASIL PERIKANAN DI DESA PULOT KABUPATEN ACEH BESAR - Yulvizar, Cut; Zaidiyah, Zaidiyah; Fahmi, Chairul; Masykur, Masykur; Misrahanum, Misrahanum; Irhamni, Irhamni; Amalia, Amalia (Universitas Syiah Kuala, 2025)
The processing activities of salted fish and peda, carried out by the Setia Bakti Women's Cooperative and the Kamboja Group, demonstrate considerable potential for further development. This potential is supported by the abundance of marine resources, the simplicity of the processing technology, the increased demand for salted fish and peda during the month of Ramadan, and the presence of numerous community-based traditional fish processors. It is imperative to ensure the shelf life of salted fish and peda, in order to maintain product quality during distribution and consumption. Salted fish has been shown to have a longer shelf life, remaining stable for up to two weeks without significant changes, whereas peda has been found to deteriorate within 25 days. This limitation can be addressed through the improvement of raw material quality, processing methods, packaging, and storage practices. The enhancement of product quality, the achievement of a more appealing flavour profile, the assurance of hygienic packaging, the provision of competitive pricing, and the elimination of the use of hazardous food additives are of paramount importance. A promising approach involves the use of natural preservatives such as chitosan, derived from shrimp, crab, and squid shells, which has the potential to extend shelf life and broaden market reach. Furthermore, the advancement of conventional fish processing can be further facilitated through structured interventions, encompassing research, training, the provision of infrastructure, and community empowerment. These interventions are designed to enhance business performance and improve the socio-economic conditions of local processors.